1995
DOI: 10.1172/jci118172
|View full text |Cite
|
Sign up to set email alerts
|

Study of the rat adrenal renin-angiotensin system at a cellular level.

Abstract: To address the question as to how zona glomerulosa (ZG) cell angiotensin II (Ang II) secretion is regulated, we developed an immuno-cell blot assay to measure its secretion from single cells. We compared these results with those obtained from population studies using a superfusion system. Modulation of Ang II secretion was investigated acutely (by administrating potassium [K+] or captopril) and chronically (by feeding the animals low or high sodium diets).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Chinese hamster ovary (CHO) cells expressing mouse renin and human angiotensinogen served as positive and negative controls. Immunoblotting was performed as described 13,14 by use of anti-mouse renin antibody, biotinylated anti-mouse IgG (DAKO Corp), and streptavidinalkaline phosphatase (DAKO) at 1:500 dilutions. Alkaline phosphatase was detected by using the chromogen NBT/BCIP (Sigma).…”
Section: Cell Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese hamster ovary (CHO) cells expressing mouse renin and human angiotensinogen served as positive and negative controls. Immunoblotting was performed as described 13,14 by use of anti-mouse renin antibody, biotinylated anti-mouse IgG (DAKO Corp), and streptavidinalkaline phosphatase (DAKO) at 1:500 dilutions. Alkaline phosphatase was detected by using the chromogen NBT/BCIP (Sigma).…”
Section: Cell Immunoblottingmentioning
confidence: 99%
“…13,14 Cells isolated from microdissected arcades of CNT secreted renin ( Figure 5A). CHO cells express- ing mouse renin ( Figure 5B) and human angiotensinogen ( Figure 5C) served as positive and negative controls, respectively.…”
Section: Cnt Cells Secrete Reninmentioning
confidence: 99%
“…A shift has occurred in recent years from an emphasis on the function of the circulating renin-angiotensin system (RAS) to a focus on the local tissue RAS in the brain, heart, peripheral blood vessels, adrenal glands, and kidney (39). Sodium restriction has been found to increase adrenal renin activity and Aldo production in parallel (8) and to increase angiotensin II (ANG II) secretion from the zona glomerulosa cells (5). Nephrectomy has been shown to increase adrenal renin activity via increased serum potassium but to decrease plasma renin to undetectable levels (8,9).…”
mentioning
confidence: 99%
“…Nephrectomy has been shown to increase adrenal renin activity via increased serum potassium but to decrease plasma renin to undetectable levels (8,9). Although some studies have shown that adrenal ANG II may be important in Aldo production through a paracrine or autocrine effect (5,24), the function of the adrenal RAS in regulating adrenal function still awaits further study.…”
mentioning
confidence: 99%
“…ANG II increases aldosterone release within minutes from adrenal cells in vitro. Under sodium depletion, the same amount of ANG II elicits a greater increase of aldosterone production than under sodium load (6). The reasons for this long-term modulation of adrenal sensitivity to rapid stimulation are complex.…”
Section: Discussionmentioning
confidence: 99%